A review of recent progresses on nickel oxide/carbonous material composites as supercapacitor electrodes - Mirzazadeh Khomambazari , Soolmaz; Lokhande, Prasad; Padervand, Saman; Zaulkiflee, Nur Dina; Irandoost, Maryam; Dubal, Sumit; Sharifan , Hamidreza (Journal of Composites and Compounds, 2022)
The rapid economic growth and enormous expansion of the portable electronics market generate a significant need for renewable energy sources, energy storage, and energy conversion technologies. Supercapacitors have emerged as a viable technology for storing renewable energy sources to meet this demand. Recently novel Transition metal oxides/carbon materials (TMC) based electrode materials attracted attention of research community working in supercapacitor field. Redox-active materials, like transition metal oxides, conductive polymers, add pseudo capacitance through quick, reversible redox reactions, and carbon-supported materials Due to their excellent physicochemical stability, large specific surface area, adaptable pore shape, and high electrical conductivity, it has been extensively utilized in supercapacitors (SCs). Of nickel oxide/active carbon composites as electrode materials for supercapacitors are examined in this review article. This review will provide a comprehensive and up-to-date summary of materials composite investigated as prospective electrode in the creation of efficient supercapacitors, along with their respective production processes and electrochemical properties addition, this article will introduce synthesis of supercapacitor electrode composite and fundamental parameters that influence supercapacitor performance.